Performance of commercial methods for linezolid susceptibility testing of Enterococcus faecium and Enterococcus faecalis. (25th May 2020) - Dejoies, Loren; Boukthir, Sarrah; Péan de Ponfilly, Gauthier; Le Guen, Ronan; Zouari, Asma; Potrel, Sophie; Collet, Anaïs; Auger, Gabriel; Jacquier, Hervé; Fihman, Vincent; Dortet, Laurent; Cattoir, Vincent
Abstract: Background: Linezolid-resistant enterococci (LRE) causing infections that are challenging to treat are rising, highlighting the need for reliable screening of LRE clinical isolates. Objectives: To evaluate the ability of the broth microdilution (BMD) method for LRE detection and to assess the performance of seven commercially available techniques for linezolid susceptibility testing. Methods: A collection of 100 clinical isolates (80 Enterococcus faecium and 20 Enterococcus faecalis ), including 20 optrA -positive isolates, 17 poxtA- positive isolates and 1 optrA / poxtA- positive E. faecium isolate, were studied. MICs were determined after 18 h [Day 1 (D1)] and 42 h [Day 2 (D2)] of incubation and interpreted following EUCAST and CLSI guidelines, which currently provide different interpretative breakpoints. Performance of commercial techniques was compared with BMD results. Results: MIC50/D1 and MIC50/D2 were both 8 mg/L, while MIC90/D1 and MIC90/D2 were 16 and 32 mg/L, respectively. MICD1 values for poxtA- positive isolates were lower than those for optrA- positive isolates. Proportions of susceptible isolates at D1 and D2 were 48% and 41%, respectively, according to EUCAST breakpoints and 35% and 13%, respectively, according to CLSI criteria (the proportions of isolates categorized as intermediate following CLSI recommendations were 13% and 28% at D1 and D2, respectively). Percentage susceptibility assessed by the commercially available techniques was always higher. The four commercial methods allowing MIC determination provided an overall essential agreement of ≥90% at D1. Categorical agreement and error rates were generally improved at D2. Conclusions: Non-automated methods (Sensititre and UMIC) and, to a lesser extent, gradient strip Etest appear to show an acceptable correlation with the BMD reference method for the detection of isolates with low MICs of linezolid after prolonged incubation.